Defect‐Driven Structural Distortions at the Surface of Relaxor Ferroelectrics. (6th May 2019) - Kong, Scarlet; Kumar, Nitish; Checchia, Stefano; Cazorla, Claudio; Daniels, John
Abstract: Relaxor‐ferroelectric materials find application in a broad range of technological devices, including ultrasonic imaging transducers, nanopositioning, and high‐performance capacitors. They generally exhibit occupationally disordered structures creating local polar fluctuations that are highly sensitive to applied electric or stress fields. The sensitivity of the material structure to external field and stress conditions also makes them likely to develop skin or surface phases that are unique from the bulk. Surface layers can adjust the material response and also lead to ambiguity in structural characterization. Here, using a combination of X‐ray diffraction methods, it is shown that a ≈20 µm skin structure commonly exists in the lead‐free relaxor‐ferroelectric ceramic (Na1/2 Bi1/2 )TiO3 –BaTiO3 . Using experiments and density functional theory calculations, it is shown that the combined action of oxygen vacancies providing internal chemical pressure and the surface plane stress state dictates the stability and structure of the skin layer. This work can be extended to all perovskite relaxor ferroelectrics and provides new insights into the origin of skin layers in these materials. The opportunity exists to further enhance the functionality of these materials through engineering of surface structures using the methods outlined here. Abstract : Surface structural distortions in relaxor ferroelectrics are demonstrated and their origin is linked to defect chemistry. The combined action of internal chemical pressure from the oxygen vacancies and a plane stress state at the surface results in a different structure than the bulk. This provides new insights into the origin of surface structures in perovskite relaxor ferroelectrics.